2016
DOI: 10.1128/aem.02583-15
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration and Microarray for Detection of Microbial Source Tracking Marker and Pathogen Genes in Riverine and Marine Systems

Abstract: Pathogen identification and microbial source tracking (MST) to identify sources of fecal pollution improve evaluation of water quality. They contribute to improved assessment of human health risks and remediation of pollution sources. An MST microarray was used to simultaneously detect genes for multiple pathogens and indicators of fecal pollution in freshwater, marine water, sewage-contaminated freshwater and marine water, and treated wastewater. Dead-end ultrafiltration (DEUF) was used to concentrate organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Indeed, Hamza and collaborators described the detection of HBoV in 41 % of river water samples (Hamza et al 2009). Also, Li and coworkers recently detected HBoV along with other enteric viruses in sewage-contaminated fresh and marine waters (Li et al 2016). Therefore, a potential role of water in the transmission of HBoV should not be neglected.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, Hamza and collaborators described the detection of HBoV in 41 % of river water samples (Hamza et al 2009). Also, Li and coworkers recently detected HBoV along with other enteric viruses in sewage-contaminated fresh and marine waters (Li et al 2016). Therefore, a potential role of water in the transmission of HBoV should not be neglected.…”
Section: Discussionmentioning
confidence: 96%
“…Li and colleagues [134] developed a custom microarray targeting pathogens, MST markers, and antibiotic resistance genes. In a subsequent study, the microarray was used to detect multiple pathogenic genes and MST markers in fresh and marine water and as well as sewage and treated effluent seeded environmental water [135]. One drawback of this approach is that it does not provide quantitative data.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, the variation in detection results at low spiking levels indicates that a level of around 10 CFU 60 l À1 is close to the detection limit of the method, which was also shown by the statistical analysis where LOD 95 was 15 CFU 60 l À1 with the confidence interval 6Á6-33 CFU 60 l À1 . Although DEUF has previously been used for Campylobacter in water (Li et al, 2016), to our knowledge we are the first to report the detection limit of DEUF for Campylobacter in water. The detection limit identified in this study agrees with previous work on other organisms, which has demonstrated that viable spores of Bacillus artrophaeus at levels of <10 CFU l À1 can be concentrated and recovered from >100 l tap water (Kearns et al, 2008) and that high recovery rates (>95%) can be obtained for Escherichia coli and human polyomavirus using DEUF (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…Although DEUF has previously been used for Campylobacter in water (Li et al, 2016), to our knowledge we are the first to report the detection limit of DEUF for Campylobacter in water. The detection limit identified in this study agrees with previous work on other organisms, which has demonstrated that viable spores of Bacillus artrophaeus at levels of <10 CFU l À1 can be concentrated and recovered from >100 l tap water (Kearns et al, 2008) and that high recovery rates (>95%) can be obtained for Escherichia coli and human polyomavirus using DEUF (Li et al, 2016). Also, Humrighouse et al (2015) determined the method detection limit for a tangential flow ultrafiltration-based automated waterborne pathogen concentrator using the same filter type as in this study.…”
Section: Discussionmentioning
confidence: 90%